2018
DOI: 10.1103/physrevb.98.235302
|View full text |Cite
|
Sign up to set email alerts
|

Polariton-enhanced exciton transport

Abstract: The transport distance of excitons in exciton-polariton systems has previously been assumed to be very small ( 1 µm). The sharp spatial profiles observed when generating polaritons by nonresonant optical excitation show that this assumption is generally true. In this paper, however, we show that the transport distances of excitons in two-dimensional planar cavity structures with even a slightly polaritonic character are much longer than expected (≈ 20 µm). Although this population of slightly polaritonic excit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
2
32
1
Order By: Relevance
“…Although the lifetime of the polaritons is around 200 ps, the time scale for this equilibration is much longer, because there is an interplay between the polariton population and the exciton reservoir with much longer lifetime. A previous study [15] has shown that excitons created by the pump laser diffuse about 30 µm away from the creation spot, but here we see evidence of reservoir excitons all the way around the ring, 150 µm from the creation spot. This indicates that polaritons may convert back into excitons via polariton-polariton collisions.…”
Section: Methodscontrasting
confidence: 46%
“…Although the lifetime of the polaritons is around 200 ps, the time scale for this equilibration is much longer, because there is an interplay between the polariton population and the exciton reservoir with much longer lifetime. A previous study [15] has shown that excitons created by the pump laser diffuse about 30 µm away from the creation spot, but here we see evidence of reservoir excitons all the way around the ring, 150 µm from the creation spot. This indicates that polaritons may convert back into excitons via polariton-polariton collisions.…”
Section: Methodscontrasting
confidence: 46%
“…One possibility is that, while the diffusion of the heavy excitons in these samples is considered to be small (of the order of ∼ 1 µm), the reservoir composed of mobile, high-momentum bottleneck polaritons could result in a significant diffusion into the centre of the trap. This possibility is supported by the recent study [28], which found the diffusion lengths of the highly excitonic polaritons at high k to be greater than 20 µm. It is also supported by the observation here and in Ref.…”
Section: Discussionmentioning
confidence: 55%
“…In this work, the ultrastrong coupling of a Bloch surface wave photon and molecular excitons in a disordered organic thin-film at room temperature is demonstrated, where the major fraction of the polaritons are propagating states. The delocalized exciton-polariton has a group velocity as high as 3×10 7 m/s and a lifetime of 500 fs, leading to propagation distances of over one hundred microns from the excitation source. The polariton intensity shows a halo-like pattern that is due to self-interference of the polariton mode, from which we derive a coherence length of 20 μm and correlate it with phase-breaking of polariton scattering.…”
mentioning
confidence: 99%
“…Thus, a promising means to improve energy transport is to strongly couple excitons with photons in an optical cavity, forming new quantum mechanical quasi-particles called excitonpolaritons. [6][7][8][9][10] Polaritons partially inherit the light effective mass and delocalization properties rendered by their photonic component, and thus are potentially immune from interactions with local defects and disorder common to molecular solids. [11][12][13] Coherent coupling with an extended and propagating photon mode can lead to rapid and long-range transport that differs from the slow and short-range diffusion of more massive excitons.…”
mentioning
confidence: 99%
See 1 more Smart Citation